2014
DOI: 10.1021/ac5010037
|View full text |Cite
|
Sign up to set email alerts
|

Redox and Label-Free Array Detection of Protein Markers in Human Serum

Abstract: A substantial outstanding challenge in diagnostics and disease monitoring is an ability to rapidly and conveniently assay for protein biomarkers within complex biological media. Label-free electroanalytical methods present, arguably, the most promising and scalable means of achieving this but, as with all label-free assays, can struggle with response selectivity issues that arise from nonspecific surface interactions. Impedimetric methods are ultrasensitive and have been applied to the quantification of a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 43 publications
(22 reference statements)
1
40
1
Order By: Relevance
“…Although somewhat counterintuitive, target binding induced increase in interfacial capacitance (and thus potentially decreased Z modulus) has been noted in prior non-faradaic assaying. 7,22 The resolved assay detection limit is 1.2 ± 0.3 pM (R 2 = 0.995) ( Figure 3B), notably lower than that previously reported for this target. 8 An initial assessment of the viability of the the synuclein/GO interface to resist biofouling was made by incubating the surface in 100% artificial serum for 30 min and then washing with water prior to each measurement.…”
Section: ■ Experimental Sectioncontrasting
confidence: 55%
“…Although somewhat counterintuitive, target binding induced increase in interfacial capacitance (and thus potentially decreased Z modulus) has been noted in prior non-faradaic assaying. 7,22 The resolved assay detection limit is 1.2 ± 0.3 pM (R 2 = 0.995) ( Figure 3B), notably lower than that previously reported for this target. 8 An initial assessment of the viability of the the synuclein/GO interface to resist biofouling was made by incubating the surface in 100% artificial serum for 30 min and then washing with water prior to each measurement.…”
Section: ■ Experimental Sectioncontrasting
confidence: 55%
“…Qi et al (2012) developed an electrochemical immunoassay array for the simultaneous detection of CEA and AFP by incorporating electrochemically addressing immobilization and one signal antibody strategy. Luo et al (2014) presented the use of thermally cross-linked poly (ethylene glycol) polymer sensory array interfaces for the ultrasensitive quantification of two protein markers (insulin and C-reactive protein). However, to the best of our knowledge, so far no related work has been reported on the development of a simple and reusable dual biosensor with the aim of simultaneous determination of Lys and IFN-γ.…”
Section: Introductionmentioning
confidence: 99%
“…9,11 In more recent work we have demonstrated that these capabilities can be incorporated into both the analysis of real patient samples and the simultaneous detection of multiple markers. 11,[17][18][19][20][21] Faradaic EIS assays are almost exclusively based on analysing the parameter of charge transfer resistance (R ct ) obtained by fitting the acquired current signal to a Randles equivalent circuit (see SI Figure 1 for details) , 22,23 while non-faradaic analyses most typically use modulus of the impedance (|Z|), double layer capacitance (C dl ) or phase (ϕ) as sampling functions. 9,[24][25][26][27] In both approaches a phenomenological model based either on an equivalent circuit 28 or continuum scheme derived from microscopic Poisson-Nernst-Plank continuum equations (using conventional or alternative approaches for diffusional activity) [29][30][31] can be applied from which physical parameters can be extracted.…”
Section: Introdutionmentioning
confidence: 99%